2018
DOI: 10.18632/oncotarget.24467
|View full text |Cite
|
Sign up to set email alerts
|

IRE1α-XBP1 inhibitors exerted anti-tumor activities in Ewing’s sarcoma

Abstract: Ewing's sarcoma (ES) is the second-most frequent pediatric bone tumor. Chromosomal translocation t(11;22)(q24:q12) results in the formation of EWS/FLI1 gene fusion, which is detected in approximately 90% of tumors of the Ewing family. Several transcriptome studies have provided lists of genes associated with EWS/FLI1 expression. However, the protein expression profiles associated with EWS/FLI1 have yet to be elucidated. In this study, to identify the regulated proteins associated with EWS/FLI1 and therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 46 publications
2
31
0
1
Order By: Relevance
“…6E). Increased XBP1s/XBP1 ratios were restored to normal levels by additional treatment with either Emapunil or the IRE1␣-XBP1 inhibitor toyocamycin (2hydroxy-1-naphthaldehyde) (Tanabe et al, 2018) (Fig. 6E).…”
Section: Emapunil Mitigates Er Stressmentioning
confidence: 94%
“…6E). Increased XBP1s/XBP1 ratios were restored to normal levels by additional treatment with either Emapunil or the IRE1␣-XBP1 inhibitor toyocamycin (2hydroxy-1-naphthaldehyde) (Tanabe et al, 2018) (Fig. 6E).…”
Section: Emapunil Mitigates Er Stressmentioning
confidence: 94%
“…Other proteomic studies have recently been carried out for soft tissue sarcomas with specific fusion genes such as EWS/FLI1 (for Ewing sarcomas) and PAX3/FOXO1 (for alveolar rhabdomyosarcoma). These studies have identified numerous proteins; 90 proteins for EWS/FLI1 and 221 proteins for PAX3/FOXO1, despite this SS study have just identified 35 proteins for SS18/SSX [48, 49]. Several functional studies have found that SS18/SSX is not a transcriptional factor but co-activator [1, 9, 43, 26, 4447].…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify the protein signatures regulated by the PAX3-FOXO1 fusion gene product in ARMS and to elucidate the function of PAX3-FOXO1, we performed proteomic analyses using isobaric tags for the relative and absolute quantitation (i-TRAQ) and determined the protein profiles regulated by PAX3-FOXO1 [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%